Detailed Potentiometric Study of Al3+ and Cr3+ with Malic Acid in Aqueous Solutions - Hamada, Yahia Z.; Harris, Marcus; Burt, Kiva; Greene, Jasmine; Rosli, Khalid (Journal of Membrane and Separation Technology, 2013)
It appeared that malic acid solubilized both Al3+ and Cr3+ in aqueous solutions at all pH-values in 0.1 M NaNO3 at 25 oC. The detailed potentiometric measurements indicated that these free tri-valent metal ions released a net of three protons (3H+’s) into the solution. Free malic acid released a net of (2H+’s) into the solution from the two carboxylates. However, in the presence of metal ions malic acid effectively releases a net of three protons (3H+’s) into the solution; two from the two carboxylates and the third from the alcoholic group. The reaction mixture of Al3+:malic acid indicated the formation of a dimeric species. The proposed structure of this dimeric species is in good agreement with what has been shown in the literature. We are presenting a dimeric species that may play an important role in malate transportation across cell membrane. Formation of the Al3+-malic acid complexes cover the span of a total of 400 mV; from +250 mV to -150 mV. The Cr3+-malic acid reaction mixture indicated the formation of a dimeric species as well.